Art-based research - McNiff, Shaun (Jessica Kingsley, 1998)
"In this book, Shaun McNiff, one of the field's pioneering educators and authors, breaks new ground in defining and inspiring art-based research. He illustrates how practitioner-researchers can become involved in art-based inquiries during their educational studies and throughout their careers, and shows how new types of research can be created that resonate with the artistic process." "Clearly and cogently expressed, the theoretical arguments are illustrated by numerous case examples, and the final part of the book provides a wealth of ideas and thought provoking questions for research."--Jacket